Selenite Protection of Tellurite Toxicity Toward Escherichia coli - Vrionis, Helen A.; Wang, Siyuan; Haslam, Bronwyn; Turner, Raymond J. (Frontiers in Molecular Biosciences, 2015)
In this work the influence of selenite on metal resistance in Escherichia coli was examined. Both synergistic and antagonistic resistance and toxicities were found upon co exposure with selenite. In wild type cells co-exposure to selenite had little effect on arsenic resistance, decreased resistance to cadmium and mercury but led to a dramatic increased resistance to tellurite of 32 fold. Due to the potential importance of thiol chemistry in metal biochemistry, deletion strains in γ-glutamylcysteine synthetase (key step in glutathione biosynthesis, encoded by gshA), thioredoxin (trxA), glutaredoxin (grxA), glutathione oxidoreductase (gor), and the periplasmic glutathione transporter (cydD) were also evaluated for resistance to various metals in the presence of selenite. The protective effect of selenite on tellurite toxicity was seen in several of the mutants and was pronounced in the gshA mutant were resistance to tellurite was increased up to 1000 fold relative to growth in the absence of selenite. Thiol oxidation studies revealed a faster rate of loss of reduced thiol content in the cell with selenite than with tellurite, indicating differential thiol reactivity. Selenite addition resulted in reactive oxygen species (ROS) production equivalent to levels associated with H2O2 addition. Tellurite addition resulted in considerably lower ROS generation while vanadate and chromate treatment did not increase ROS production above that of background. This work shows increased resistance towards most oxyanions in mutants of thiol redox suggesting that metalloid reaction with thiol components such as glutathione actually enhances toxicity of some metalloids.